Identification of snow mold tolerance QTL in a landrace winter wheat using linkage mapping. Issue 4 (6th June 2022) - Phipps, Savannah N.; Burke, Adrienne B.; Balow, Kerry; Smith, Jared; Murray, Timothy; Carter, Arron H.
Abstract: In areas of the Pacific Northwest (PNW), snow mold, a fungal disease with multiple causal agents, can have severe impacts on winter wheat ( Triticum aestivum L. subsp. aestivum ) yields. Growing tolerant varieties is the best option to manage the disease; however, genetic diversity for the trait is limited in local varieties. The winter wheat landrace PI 173438 has been used in Japan to improve snow mold tolerance but has not been used in PNW breeding programs. A doubled haploid population from a cross between PI 173438 and susceptible variety WA 8137 was used to identify novel quantitative trait loci (QTL) associated with snow mold tolerance that would be validated using marker‐assisted selection (MAS) in two separate populations. A linkage map was developed using genotypic data collected on the PI 173438/WA 8137 population, which was then used with phenotypic data in composite interval mapping for QTL analysis. Six QTL were found associated with snow mold tolerance traits, five of which originated from PI 173438. A QTL was found on chromosome 1D that has not been reported before. The remaining QTL occurred on chromosomes that were previously reported to have snow mold tolerant QTL, some of which may be identical. Several of these QTL and linked markers were suitable for testing via MAS on separate populations revealing no significant difference amongst the three or four QTL that could be tested. Such results continue to indicate the complexity of breeding for snow mold tolerance using molecular markers. Core Ideas: PI 173438 was found to possess novel QTL associated with snow mold tolerance. Complexity in snow mold tolerance contributed to challenges in validating the QTL. Marker‐assisted selection is still difficult to use in wheat on quantitative traits like snow mold tolerance.